Virtual Teams: Human Resources’ technology preferences for better communication, increased trust and performance. - Duarte, Isabel; Cunha, Luís (Revista Lusófona de Economia e Gestão das Organizações, 2015)
AbstractVirtual Teams (VTs) are increasingly being adopted by companies. Being geographicallyand time dispersed, human resources of VTs are totally dependent upon the use ofinformation and communication technologies (ICT) to support their communicationalsuccess. Although much research has already been done on several aspects of VirtualTeams, very little has focused on the relation between the virtual team communicationperformance and the selection of tools available to the team members. Additionally,most of the theories related to tool selection concentrate in the combined characteristicsof task and technology, disregarding human factors based in personal characteristics,comfort and preferences.To detect which technology workers of Virtual Teams prefer for accomplishing eachone of their communicational needs and to analyze the impact of personal characteristicsbased technology choice, on cohesion, leadership, knowledge share and trust,leading to virtual team performance, an electronic questionnaire has been sent tomembers of virtual teams in several companies from different sectors of activity, and79 valid answers were received.The analysis looked at the data from different perspectives: Is there, globally, a preferredtechnology? Do personal characteristics of workers - Gender, Age Group, EducationLevel and IT use Proficiency – influence the choice? And, does the choice ofthe preferred technological tool that best suits each of the four HRM themes – Trustbuildup, Management, Knowledge Share and Cohesion – follow the global preference?The results have shown that e-Mail is the preferred technology choice and that thischoice is not influenced by gender. The other three sets of personal characteristicsinfluence the choice. For building Trust and Cohesion, the preferred technology is videoconference,contradicting the global tendency whereas for Knowledge Share andfor Management activities e-Mail is again the preferred technology, in line with themain choice.Keywords: virtual teams, communication technology, channel selection, human resources,cohesion, trust, performanceResumoA adoção de Equipas Virtuais pelas empresas tem vindo a aumentar. Encontrandosedispersos, geograficamente e no tempo, os recursos humanos das equipas virtuaisdependem totalmente da utilização de tecnologias de informação e comunicação (TIC)para suportar as suas necessidades comunicacionais. Embora exista muita investigaçãoefetuada sobre inúmeros aspetos das equipas virtuais, muito pouca se focou narelação entre o desempenho comunicacional destas e a seleção das ferramentas disponíveispara os membros. Além disso, a maior parte das teorias relacionadas com aselecção de ferramentas concentra-se na combinação de características tarefa/tecnologia,descurando factores humanos baseados nas características pessoais, no confortoe nas preferências.Com o fim de detetar qual a tecnologia preferida pelos trabalhadores das equipas virtuaispara a satisfação das suas necessidades comunicacionais e ainda para analisaro impacto da escolha tecnológica - baseada em características pessoais - na confiança,coesão, liderança e partilha de conhecimento foi enviado um questionário eletrónicoa membros de equipas virtuais de empresas operando em diferentes sectores, tendosido recebidas 79 respostas válidas.A análise dos dados centrou-se em diferentes perspetivas: Existe uma tecnologia preferida?As caraterísticas pessoais dos trabalhadores – género, faixa etária, escolaridade ecapacidade de utilização de tecnologia – influenciam a escolha? A escolha da tecnologiaque melhor se adapta a cada um dos 4 temas de GRH - confiança, coesão, liderançae partilha de conhecimento – segue a preferência global?Os resultados mostraram ser o e-Mail a tecnologia preferida e que esta escolha nãoé afetada pelo género. Os outros três tipos de caraterísticas pessoais mostraram terinfluência na seleção da tecnologia. Para o estabelecimento de confiança e coesão, atecnologia preferida foi a vídeo-conferência enquanto para a partilha de conhecimentoo e-Mail voltou a ser a escolha principal.Palavras chave: equipas virtuais, tecnologia de comunicação, seleção de canais, recursoshumanos, coesão, confiança, performance